2017
DOI: 10.1007/s10803-017-3265-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Pragmatic Language in Children with ASD: Longitudinal Impact on Anxiety and Externalizing Behaviors

Abstract: Children with autism spectrum disorder (ASD) are at heightened risk for developing comorbid psychological disorders, including anxiety disorders, which may be further exacerbated by the presence of externalizing behaviors. Here, we examined how structural language and pragmatic language predicted anxiety and externalizing behaviors. Participants were 159 young children (4-7 years old) with ASD and their mothers. Utilizing structural equation modeling we examined associations among structural language, pragmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…Similarly, a study that included 159 children with ASD aged between 4 and 7 years reported that while structural language positively predicted anxiety level, pragmatic language was inversely related to anxiety and externalizing behaviors. 37 In addition, the authors found that the more structural language preceded pragmatic language, the more prone children were to exhibit anxiety symptoms.…”
Section: Sci Groupmentioning
confidence: 99%
“…Similarly, a study that included 159 children with ASD aged between 4 and 7 years reported that while structural language positively predicted anxiety level, pragmatic language was inversely related to anxiety and externalizing behaviors. 37 In addition, the authors found that the more structural language preceded pragmatic language, the more prone children were to exhibit anxiety symptoms.…”
Section: Sci Groupmentioning
confidence: 99%
“…The construct of pragmatic language is complex, and a consensus definition has not been established in the literature. Early theoretical work describes pragmatics as the use of language appropriate to the social context (Prutting and Kirchner, 1987); however, more recent conceptual work recognizes an interconnection between pragmatics, social cognition and emotional understanding (Fujiki et al, 2002; Adams et al, 2005; Rodas et al, 2017). For example, social cognition has been associated with conversation skills, but the nature of the relationship between the two constructs is unknown (Matthews et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Law, Rush, and McBean (2014), by contrast, reported that pragmatic abilities partially mediated the relationship between language difficulties and problem behavior in their sample of primary school children recruited from socially disadvantaged backgrounds. Also in a group of 4-to 7-year-old children with ASD, pragmatic language deficits were clearly associated with child anxiety and externalizing problems, whereas the relation with structural language skills was relatively small for anxiety and absent for externalizing problems (Rodas, Eisenhower, & Blacher, 2017). In a recently published longitudinal study on the abilities of children initially referred for language concerns, Roy and Chiat (2014) used the Social Responsiveness Scale (SRS: Constantino & Gruber, 2005) to measure social-communicative ability.…”
Section: Pragmatic Difficulties As Additional Predictormentioning
confidence: 99%